1262. Investigation and Mitigation of a Multi-Species Outbreak of Invasive Fungal Infections on Two Oncology Wards. (26th November 2018) - Huslage, Kirk; Stiegel, Matthew; Lobaugh-Jin, Erica; Hnat, Amy; Strittholt, Nancy; Lewis, Sarah S; Baker, Arthur W; Thomann, Wayne R; Smith, Becky
Abstract: Background: We investigated an increase in hospital-acquired invasive fungal infections (HA-IFI) among patients admitted to adjacent hematopoietic stem cell transplant (HSCT) and hematologic malignancy (HM) wards in the setting of a large construction project adjacent to the hospital. Methods: We defined cases of HA-IFI as HSCT or HM patients who met criteria for probable or proven IFI with suspected inpatient acquisition. We hypothesized that outside construction increased internal particle/spore counts despite preconstruction prevention efforts. The environmental investigation included an evaluation of storage/distribution of supplies, air handler inspections, air particulate counts, and bioaerosol sampling of airborne fungal spores. Results: From October 2017 to January 2018, 11 cases of probable/proven HA-IFI occurred (Figure 1). Infections caused by multiple pathogens (Figure 2) ranged from pneumonia and sinusitis to disseminated disease. Bioaerosol sampling and particulate counts were taken from unit corridors and rooms on both wards. Fungal species identified via bioaerosol sampling were primarily Penicillium and Cladosporium species, with rare Aspergillus identified. Geometric mean particulate counts of 1 μm aerodynamic size were reduced by 88% and 75% on the HM and HSCT wards, respectively (Figure 3). Interventions on these units occurred from January to February 2018 and included: limiting the frequency of outdoor air exchanges on air handler units, reinforcing seals around entrance doors, adjusting room pressurizations to be positive or neutral on HM ward (HSCT ward is already a positive pressure environment), eliminating cardboard associated with supplies, and requiring N95 respirators for HSCT patients when off unit. After implementing these environmental control measures, we have not identified additional cases of HA-IFI on these wards. Conclusion: We describe a multispecies outbreak of IFI in HM and HSCT patients potentially associated with new building construction that occurred despite implementation of multiple pre-construction control efforts. A multifaceted strategy to improve air quality and protect patients on and off high-risk units was needed to mitigate the outbreak. Disclosures: All authors: No reported disclosures.